ChemInform Abstract: Lewis Acid Catalyzed C‐3 Alkylidenecyclopentenylation of Indoles: An Easy Access to Functionalized Indoles and Bisindoles. Issue 36 (September 2015) - Sarath Chand, S.; Sasidhar, B. S.; Prakash, Praveen; Sasikumar, P.; Preethanuj, P.; Jaroschik, Florian; Harakat, Dominique; Vasse, Jean‐Luc; Radhakrishnan, K. V.
Abstract The title compounds are efficiently obtained in one‐pot by ring opening of pentafulvene derived diazabicyclic olefins.